The Influence of Work Environment Conditions and Social Interaction on Job Satisfaction (Study of MTs Al Muttaquun Wates) - Kristanti, Desi; Laely, Nur; Herlina, Intan Arum; Saputra, Moch. Arviyan (PT FORMOSA CENDEKIA GLOBAL, 2024)
Employee job satisfaction is an important factor in influencing the overall success of an organization. One thing that can affect job satisfaction is favorable work environment conditions and social interactions. This study was done to determine the effect of work environment conditions and social interactions on job satisfaction at MTs Al Muttaquun Wates. The population in this study was 30 educators or teachers. The study uses the explanatory quantitative method. The method used is multiple linear regression analysis using IBM SPSS 26. The study showed that partial work environment conditions did not affect job satisfaction, while social interactions affected job satisfaction. Simultaneously, work environment conditions and social interactions did not affect job satisfaction.